Elements of geographical hydrology - Knapp, Brian J. (Allen & Unwin, 1979)
This is a concise introduction to principles and applications of hydrology in a geographical context. It uses a wealth of fully illustrated examples to relate theory to the real geographical problems associated with a subject central to our understanding of the natural environment and the use we make of it.\Whilst hydrology and the study of water resources have been established for sometime as topics for advanced study, they have been introduced into A-level syllabuses only recently. Elements of Geographical Hydrology is one of the first books aiming to serve the specific requirements at this level. It provides a sound introduction to the theory and principles of hydrology and illustrates them by means of examples. It then proceeds to show the relevance of hydrology to several important aspects of geography, namely: soil studies, hillslope development, and water resource management. It relies throughout on detailed examples, an approach which should enliven the subject and provide substantial material to bring home its realities and reinforce the reader's understanding.\The book is fully illustrated with many line drawings and photographs, all of which are closely linked with the text. It offers opportunities for the reader to test his or her understanding of the subject by means of problem exercises. A selected and annotated list of further reading indicates the most useful and accessible sources of more comprehensive and advanced material.